6ER-012 Treatment of patients with metastatic castration-resistant prostate cancer with abiraterone and enzalutamide: a retrospective study. (2nd March 2018) - Santos, R; Pereira, B; Morgado, M
Abstract : Background: Prostate cancer is the most common malignancy and the third leading cause of cancer death in males both in Portugal and in Europe. Currently, there are a variety of options available for the treatment of metastatic castration-resistant prostate cancer (mCRPC), as is the case with abiraterone and enzalutamide, focused on this analysis. Purpose: To analyse the characteristics, treatment and outcomes of patients receiving mCRPC treated with abiraterone or enzalutamide, and correlate with progression-free survival and overall mean survival. To evaluate the influence of the variables age, Gleason score, duration of previous antineoplastic treatment and PSA at the beginning of treatment in response to treatment. Material and methods: A retrospective study, based on data from the introduction of these drugs in the hospital, in November 2013, until 31 July 2017, was performed at our hospital. Several variables were analysed through consultation of the clinical processes such as age, Gleason score, metastatic existence or not, previous antineoplastic therapies, associated therapeutics, comorbidities, chemotherapy-naive or post-chemotherapy patients, PSA at the beginning of treatment and duration of treatment. Results: The sample consisted of 21 mCRPC patients without prior chemotherapy. The mean age of the patients was 72.1 years (52–90 years). There was no statistically significant difference (p>0.05) between abiraterone and enzalutamide in the percentage of patients with a 6 month PSA reduction ≥50% (i.e., progression-free survival), or in the overall mean survival (23.2 months (95% CI: 16.2 to 30.2) for abiraterone vs 19.1 months (95% CI: 14.7 to 23.5) for enzalutamide). Likewise, a significant influence (p<0.05) of the following analysed variables was not observed in treatment outcomes: patients' age at 6 month PSA reduction ≥50%; Gleason score in the mean value and distribution of PSA reduction (%) at 6 months; previous antineoplastic treatment (≥12 months) in the mean value and distribution of PSA reduction values (%) at 6 months; and PSA value at baseline in the proportion of patients with 6 month PSA reduction ≥50%. Conclusion: Treatment with abiraterone or with enzalutamide did not lead to significant differences in the outcomes (progression-free survival or overall mean survival) of patients with mCRPC without prior chemotherapy. Likewise, none of the analysed variables significantly influenced treatment outcomes. No conflict of interest